ANALYSIS OF HOMESTAY LODGING PROMOTION IN MANINJAU VILLAGE - Nabilla Almira Lamis; Yuliana Yuliana; Feri Ferdian (JELAJAH: Journal of Tourism and Hospitality, 2022)
Homestay in Maninjau Village is a simple type of lodging that only relies on a few rooms to be rented out to tourists and managed by the community. The purpose of this study is to analyze how homestay inn managers in Maninjau Village promote their lodging in terms of the media used and how homestay inn managers in Maninjau Village promote their lodging in terms of the manager's accuracy in choosing and using promotional media. Data collection techniques used are interviews, observation, and documentation. The informant determined in this study is Purpose Sampling, which is a technique of collecting data sources that are needed with certain considerations. The type of research used is descriptive with qualitative data consisting of five indicators, namely Advertising/Marketing, Personal Sales, Sales Promotion, Public Relations, and Word of Mouth. Data collection techniques used are interviews, observation, and documentation. It was concluded that there were two findings obtained. The general finding is that homestay managers in Maninjau Tourism Village have begun to understand that promotion is very important to increase homestay income. Managers have used advertising promotion media both in print media using business cards or relying on the internet. Managers are also starting to understand how they can promote homestays in a very simple way. Even so, there is a need for monitoring and increasing knowledge about promotion. Not only with hardcopy media and the internet, but promotions also require suggestions, comments, and criticisms to help improve homestay shortcomings and minimize the same mistakes in the future.